n-GaAs Band-Edge Repositioning by Modification with Metalloporphyrin/Polysiloxane Matrices - Hikmat S. Hilal; Moayyad Masoud; Samar Shakhshir; Najeh Jisraw (Active and Passive Electronic Components)
Tetra(-4-pyridyl)porphyrinatomanganese(III)sulfate, MnP, (in the forms of MnIII and MnII mixture), was embedded into a polysiloxane polymer matrix and attached to the surfaces of n -GaAs wafers. The n-GaAs/polymer/MnP system was annealed under nitrogen and used for photoelectrochemical study in water/LiCIO4/Fe(CN)63-/Fe(CN)64− system. The results indicated a positive shift in the value of the flat-band potential of the semiconductor due to MnP. This was manifested by shifting the values of the dark-current onset potential and the photo-current open-circuit potential towards more positive values. These findings are potentially valuable in future applications of solar energy in hydrogen and oxygen production from water.